2023
DOI: 10.3390/ncrna9020026
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Age-Related Proteostasis and Stress Responses

Abstract: Aging is associated with the accumulation of damaged and misfolded proteins through a decline in the protein homeostasis (proteostasis) machinery, leading to various age-associated protein misfolding diseases such as Huntington’s or Parkinson’s. The efficiency of cellular stress response pathways also weakens with age, further contributing to the failure to maintain proteostasis. MicroRNAs (miRNAs or miRs) are a class of small, non-coding RNAs (ncRNAs) that bind target messenger RNAs at their 3′UTR, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 205 publications
0
3
0
Order By: Relevance
“…However, here we show that, amongst such protein folding factors, DNAJB5, HSP90AB1, CALR, and CDC37 all exhibit increased levels in the cytoplasm of hTDP-43 ΔNLS -positive neurons in the primary motor cortex of rNLS8 mice at disease onset. Further, we demonstrate that this increase in abundance is mediated by currently uncharacterized post-transcriptional mechanisms (possibly via non-coding RNAs 70 or RBPs 71 ), given that there was no increase in transcript level to correlate with the heightened protein abundance. Previous studies have also reported a divergence of protein levels from RNA levels of some HSPs, with increases in HSPB1 in SOD1 G93A mice being accompanied by no change in Hspb1 transcripts 72 .…”
Section: Discussionmentioning
confidence: 75%
“…However, here we show that, amongst such protein folding factors, DNAJB5, HSP90AB1, CALR, and CDC37 all exhibit increased levels in the cytoplasm of hTDP-43 ΔNLS -positive neurons in the primary motor cortex of rNLS8 mice at disease onset. Further, we demonstrate that this increase in abundance is mediated by currently uncharacterized post-transcriptional mechanisms (possibly via non-coding RNAs 70 or RBPs 71 ), given that there was no increase in transcript level to correlate with the heightened protein abundance. Previous studies have also reported a divergence of protein levels from RNA levels of some HSPs, with increases in HSPB1 in SOD1 G93A mice being accompanied by no change in Hspb1 transcripts 72 .…”
Section: Discussionmentioning
confidence: 75%
“…Epigenetic dysregulation is a part of the aging process, and many nutraceuticals are regarded as promising candidates to counteract these age-related epigenetic changes ( Bacalini et al, 2014 ). Likewise, changes in miRNA expression play a prominent role in regulating the mRNA expression of genes involved in the shaping of aging and age-related diseases ( Matai and Slack, 2023a ). Therefore, it’s expected that diets or nutraceuticals that control specific miRNA expression can enhance healthy aging or halt the progression of age-related diseases.…”
Section: Implications For Prevention and Treatment Of Age-related Dis...mentioning
confidence: 99%
“…Cardiovascular disease, neurological illness, and cancer are only a few of the age-related ailments linked to miRNA dysregulation ( Quinlan et al, 2017 ; Kinser and Pincus, 2020 ). New therapeutic intervention opportunities may arise from a better understanding of miRNAs’ roles in aging and age-related diseases ( ElShelmani et al, 2021a ; Matai and Slack, 2023b ).…”
Section: Introductionmentioning
confidence: 99%